Upaya Pengembangan Moral Melalui Bercerita Dengan Media Wayang Pada Kelompok B Tk Aisyiyah Pucangan 1 Kartasura Tahun Ajaran 2016/2017 - Faizah, Ism iNuril; , Drs. Amrul Choiri,.M.Ag (2017)
Storytelling is a manner speak and deliver a story or give an explanation orally. Equally important the storytelling is a manner deliver the values that prevailed in society. In any case, storytelling can use medias. One of them is using a puppet in order to more interest to kindergartens. Using the puppet can train children's spiritual, deliver moral and religion values, train imagination and illusion, train an emotion and self identification, increase an experience and entertainment. The object of this research was improving of moral through storytelling by puppet in groups B TK Aisyiyah Pucangan 1 Kartasura in Academic Year 2016/2017. This research was a classroom action research, in this situation the design of research summarized in three steps sunch as Pre-cyclical, cyclical 1, cyclical 2. The technique of accumulation data use observation and documentation. The result of calculation was each of cyclical developed moral through storytelling with puppet media abaout 44,22% in Pre-Cycal, 74,44% in cyclical 1, and 84,46% in cyclical II. Based on the calculation of the improving of moral through storytelling by puppet in groups B at TK Aisyiyah Pucangan 1 Kartasura in Academic Year 2016/2017 as was success because it had passed target in research that determined about 80%. Keyword: Improving of Moral, Storytelling by Puppet